Algorithmic Approach To Contemporary Da'wah Through SEO Optimization And Audience Engagement On Barakka’na Mangkoso YouTube - Hasan, Abdul Rahman; Iskandar , Iskandar; Qadaruddin, Muhammad; Ramli, Ramli; Sulvinajayanti, Sulvinajayanti; Nasriah, St. (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Digital technology has transformed Islamic da'wah, positioning YouTube as a key platform where effectiveness depends on the quality of religious content, SEO alignment, algorithmic literacy, and audience engagement strategies in contemporary digital society. This study examines the role of algorithmic optimization in reshaping contemporary Islamic da'wah through a qualitative single-case study of the YouTube channel Barakka’na Mangkoso (South Sulawesi, Indonesia). Data were collected through in-depth interviews, digital observation of YouTube content, and analysis of YouTube Analytics documents. Data analysis employed interactive processes of data condensation, data display, and conclusion drawing. Findings reveal that algorithmic logic has become constitutive of digital da'wah, fundamentally influencing content structure, pacing, and thematic selection. However, strict ethical guardrails prohibiting deceptive clickbait and transactional promises, combined with deep Bugis cultural rootedness, enable the channel to expand reach dramatically without compromising religious authenticity. The study concludes that effective contemporary da'wah now requires dual competence in religious scholarship and algorithmic literacy, offering a replicable model for other preachers and institutions seeking to amplify authentic Islamic messages in the platformized public sphere. The study concludes that effective digital da'wah requires integrating algorithmic literacy with Islamic scholarship and employing ethical, culturally grounded strategies to expand reach without compromising religious authenticity.